Klasterisasi Siswa Sekolah Menengah Atas Berdasarkan Kemampuan Literasi Matematis dan Kemampuan Numerasi - Azkannaila, Ara; Lestari, Karunia Eka (Papanda, 2025)
Mathematical literacy is the ability of an individual to formulate, apply, and interpret mathematics in various contexts. Meanwhile, numeracy is the ability used to utilize numbers and arithmetic operation skills to solve numerical problems in the real world. Learning in the classroom must certainly be planned as well as possible and is one of the challenges for teachers in order to provide learning that is in accordance with the characteristics and needs of students. Therefore, this study aims to categorize students based on mathematical literacy and numeracy skills in order to map the pattern of student characteristics based on these two abilities. The approach of this research is quantitative with quantitative descriptive method, while the population of this research is class XI students of SMA Negeri 1 Tegalwaru with a sample of 96 students from three classes. The data collection technique used test instruments and data analysis was carried out by applying the k-means algorithm at the data mining stage. The results explained that students were divided into two clusters where cluster one contained 24 students and cluster two totaled 72 students. Cluster one consists of students who understand quite well in mathematical literacy skills, and cluster two consists of students who understand numeracy skills quite well. Based on the discussion, the conclusion of this study is that the characteristics of students are divided into two clusters in which researchers recommend learning models related to visuals and media such as picture to picture, as well as learning that can construct problems and student understanding, namely discovery learning models and problem-based learning models.